THE EFFECT OF RESTAURANT ATMOSPHERE AND SERVICE QUALITY ON CUSTOMER PURCHASE INTENTION (CASE STUDY OF DANAU TONDANO RESTAURANT) - Worek, Ronaldo Maesa (Sam Ratulangi University, 2015)
ABSTRACT Services are rapidly becoming a larger portion of many organizationsâ regionally, nationally, and globally and are considered as a tool for revenue streams. There are lot types of business that offers service quality and store atmosphere and one of them is restaurant. The sample of this research is the consumer of Danau Tondano Restaurant. The samples taken are 70 respondents. This research is a causal research and the data are gathered from using questionnaires and used multiple regression analysis. This research concludes that there is a significant effect of restaurant atmosphere and service quality on customer purchase intention simultaneously. But partially the effect of restaurant atmosphere on customer purchase intention is significant while the effect of service quality on customer purchase intention is not significant. Danau Tondano Restaurant should invest more on the appearance of the restaurant itself in order to increase the restaurant atmosphere. Keywords: Restaurant Atmosphere, Service Quality, Customer Purchase Intention.